2016
DOI: 10.18632/oncotarget.13240
|View full text |Cite
|
Sign up to set email alerts
|

Laricitrin ameliorates lung cancer-mediated dendritic cell suppression by inhibiting signal transducer and activator of transcription 3

Abstract: Natural polyphenolic compounds of grapes and their seeds are thought to be therapeutic adjuvants in a variety of diseases, including cancer prevention. This study was carried out to investigate the effect of grape phenolic compounds on the regulation of cancer-mediated immune suppression. Laricitrin exhibits the greatest potential to ameliorate the suppressive effects of lung cancer on dendritic cells’ (DCs’) differentiation, maturation and function. Human lung cancer A549 and CL1-5 cells change the phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Frustratingly, accumulated evidence has suggested that tumor cells could suppress the immunological function of infiltrated DCs through the secretion of chemokines and cytokines, as well as inflammatory factors. Chang et al reported that tumor-infiltrating DCs are always functionally deficient [23]. Consistently in this study, we found that TCM-pretreated DCs expressed a lower frequency of maturation markers, including CD80, CD83, CD86, CD40 and MHC-II, compared with NHA mediumpretreated DCs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Frustratingly, accumulated evidence has suggested that tumor cells could suppress the immunological function of infiltrated DCs through the secretion of chemokines and cytokines, as well as inflammatory factors. Chang et al reported that tumor-infiltrating DCs are always functionally deficient [23]. Consistently in this study, we found that TCM-pretreated DCs expressed a lower frequency of maturation markers, including CD80, CD83, CD86, CD40 and MHC-II, compared with NHA mediumpretreated DCs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The STATs pathway has been shown to play an essential role in the downregulation of inflammatory responses in AD ( Bao et al ., 2013 ; Chang et al ., 2016 ). Activation of STAT3 resulted in increased release of TNF-α, IL-10, IL-1β ( Zhang et al ., 2015 ; Drennan et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The STAT pathway plays an important role in blocking the inflammatory responses in AD [42]. Activation of STAT3 is responsible for increased expression of COX-2 and iNOS [43].…”
Section: Discussionmentioning
confidence: 99%